2014
DOI: 10.26444/jpccr/71458
|View full text |Cite
|
Sign up to set email alerts
|

Maxillofacial trauma in relation to patients’ sobriety – a one-year epidemiological analysis

Abstract: Introduction. The maxillofacial skeleton protects the areas particularly susceptible to injuries. Maxillofacial fractures occur when the force of an injury exceeds the biomechanical bone tolerance. Excessive alcohol consumption evokes violence, brutality and assault and other harmful human behaviour. Alcohol abuse seems to be crucial in evoking situations resulting in severe maxillofacial traumas or permanent disability. Objective. The aim of the study was an epidemiological analysis of patients admitted to ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Previous research has identified that individuals with high levels of alcohol consumption are at greater risk for traumatic brain injury from head injury compared with the general population and men are more likely to experience wound/ laceration of the head than women. 26 Several studies have shown that alcohol intoxication has a strong association with the incidence of facial/head injuries, 5,27,28 which may result from aggression, violence, falls, a tendency to fight and other risky behaviours. 28 In an Australian study, interpersonal violence related to alcohol consumption was the most common cause of facial fractures, followed by falls and transport-related injuries, and the male gender accounted for the majority of these incidents, 29 which was consistent with this study.…”
Section: Main Associated Presentationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has identified that individuals with high levels of alcohol consumption are at greater risk for traumatic brain injury from head injury compared with the general population and men are more likely to experience wound/ laceration of the head than women. 26 Several studies have shown that alcohol intoxication has a strong association with the incidence of facial/head injuries, 5,27,28 which may result from aggression, violence, falls, a tendency to fight and other risky behaviours. 28 In an Australian study, interpersonal violence related to alcohol consumption was the most common cause of facial fractures, followed by falls and transport-related injuries, and the male gender accounted for the majority of these incidents, 29 which was consistent with this study.…”
Section: Main Associated Presentationsmentioning
confidence: 99%
“…26 Several studies have shown that alcohol intoxication has a strong association with the incidence of facial/head injuries, 5,27,28 which may result from aggression, violence, falls, a tendency to fight and other risky behaviours. 28 In an Australian study, interpersonal violence related to alcohol consumption was the most common cause of facial fractures, followed by falls and transport-related injuries, and the male gender accounted for the majority of these incidents, 29 which was consistent with this study.…”
Section: Main Associated Presentationsmentioning
confidence: 99%